Necrotizing periodontal diseases. Part. I - Maita Veliz, Luis (2014)
Necrotizing periodontal Diseases and Conditions in 1999 are two: Necrotizing gingivitis (NG) and Necrotizing periodontitis (NP). Necrotizing stomatitis (NE) is a more aggressive variation, which can be linked to the two entities mentioned. In this review we discuss their definitions, etiology, clinical aspects, diagnosis and treatment, trying to clarify these points with updated concepts.